Implementasi Filsafat Pendidikan Islam Dalam Pembelajaran Tahfidzul Qur’an Di Mi An Nuur Jatikuwung - Fikri Jayyid, Difa’ul; Mujiburrohman (CV. SINAR HOWUHOWU, 2025)
This study aims to examine in depth the implementation of Islamic educational philosophy values in the learning of tahfidzul Qur'an at Madrasah Ibtidaiyah (MI) An Nuur Jatikuwung. The main focus of this study is how the basic values in Islamic educational philosophy, namely ubudiyah (servitude to God), khalifah (leadership), ahsan (optimization of good deeds), adil (justice), and mas'uliyah (responsibility) are actualized in learning strategies, curriculum management, and character building of students. The approach used is descriptive qualitative with field observation methods in the learning process of tahfidzul Qur'an and in-depth interviews with two tahfidz teachers and the head of the madrasah. The results of the study indicate that these values are not only a conceptual foundation in institutional documents, but have been internalized in a humanistic, spiritual, and character-oriented learning culture. The tahfidzul Qur'an learning model at MI An Nuur is evidence that the integration between Islamic educational philosophy and pedagogical practices can create comprehensive, contextual, and transformative education.